An Opportunity for All : Venezuelan Migrants and Refugees and Peru's Development - World Bank (World Bank, Lima, 2019)
Faced with the Venezuelan exodus of unprecedented magnitude in recent Latin American and Caribbean history, the main objective of this study is to determine the social, economic and sectoral implications that this phenomenon is having on Peru, in order to inform the public policy agenda with a view to development. The study presents an analysis which characterizes the different dimensions of the Venezuelan migration to Peru: from the trajectory to the country, the institutional reception and response framework, opportunities and challenges for social integration, gender dynamics, and the Venezuelan population’s access to services and insertion into the labor market. The analysis also provides recommendations that seek to contribute to the strengthening of a humane and orderly migration management, and to capitalize on the potential of an adequate integration of the migrant and refugee population in Peru.